Production Improves Recognition and Reduces Intrusions in Between-Subject Designs: An Updated Meta-Analysis. - Fawcett, Jonathan M.; Baldwin, Maddison M.; Whitridge, Jedidiah W.; Swab, Michelle; Malayang, Kyla; Hiscock, Brooke; Drakes, Dalainey H.; Willoughby, Hannah V. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2023)
The production effect refers to the finding that words read aloud are better remembered than those read silently. This pattern has most often been explained as arising from the incorporation of sensorimotor elements into the item representation at study, which could then be used to guide performance at later test. This theoretical framework views aloud items as being distinctive in relation to silent items, and thus the effect was thought to emerge only when production was manipulated within-subjects. This claim was later challenged, and a reliable (albeit smaller) between-subject production effect has since been shown in recognition memory. Across a series of meta-analyses, we extend this earlier work, replicating the between-subject production effect for recognition, and demonstrating no such effect for overall target recall. However, supporting recent theoretical claims, we further observed an interaction between the production effect and serial position within recall, such that a production effect was observed for late time points but not early time points (a similar, albeit smaller and noncredible trend was observed for recognition). Finally, we provide evidence that production reduces off-list intrusions. In summary, production has a reliable impact on recognition memory when manipulated between-subjects, but a more complex relationship with recall performance.